2017
DOI: 10.1002/jcp.26243
|View full text |Cite
|
Sign up to set email alerts
|

CpG oligodeoxynucleotide preconditioning improves cardiac function after myocardial infarction via modulation of energy metabolism and angiogenesis

Abstract: Unmethylated CpG oligodeoxynucleotide (CpG-ODN), a Toll-like receptor 9 (TLR9) ligand, has been shown to protect against myocardial ischemia/reperfusion injury. However, the potential effects of CpG-ODN on myocardial infarction (MI) induced by persistent ischemia remains unclear. Here, we investigated whether and how CpG-ODN preconditioning protects against MI in mice. C57BL/6 mice were treated with CpG-ODN by i.p. injection 2 hr prior to MI induction, and cardiac function, and histology were analyzed 2 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…The activation of angiogenesis represents another requisite aspect of restoration initiated after myocardial ischaemic injury. Increasing angiogenesis in infracted tissue was demonstrated to occur after pre‐conditioning using CpG ODNs, restoring myocardial function after I/R in a very recent study by Zhou et al . In line with this, our study identified a set of genes with specific implications for the fostering of angiogenesis to be significantly up‐regulated in TLR9‐pretreated mice.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The activation of angiogenesis represents another requisite aspect of restoration initiated after myocardial ischaemic injury. Increasing angiogenesis in infracted tissue was demonstrated to occur after pre‐conditioning using CpG ODNs, restoring myocardial function after I/R in a very recent study by Zhou et al . In line with this, our study identified a set of genes with specific implications for the fostering of angiogenesis to be significantly up‐regulated in TLR9‐pretreated mice.…”
Section: Discussionsupporting
confidence: 86%
“…Increasing angiogenesis in infracted tissue was demonstrated to occur after pre-conditioning using CpG ODNs, restoring myocardial function after I/R in a very recent study by Zhou et al 47 In line with this, our study identified a set of genes with specific implications for the fostering of angiogenesis to be significantly up-regulated in TLR9-pretreated mice. Among the leading up-regulated genes we discovered were S100A9, S100A8, ARG1, CFB and CCL2, all of which have been demonstrated to exert specific positive influences on cardiovascular angiogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…The deficiency of TLR9 led to a decreased survival rate and increased mortality due to acute cardiac rupture, which was expressed as fewer myofibroblast formation and reductions of collagen I in the peri-infarct area, moreover, the thinner wall thickness and less fibrotic area. Prior studies and our results have documented the cardiovascular-protection of TLR9 ligand ODN 1826 in experimental MI 14 , we illustrated that the positive role of TLR9 ligand in wound healing. Therefore, the early activation of smad3 by TLR9 leads to the reparative fibrotic response in vivo, which resulted in normal accumulation of myofibroblast in the infarct area and synthesis and maturation of the extracellular matrix.…”
Section: Discussionsupporting
confidence: 77%
“…Also, the presence of immune cells, like macrophages and neutrophils leads to the release of cytokines that are capable of stimulating fibroblast growth factor and VEGF expression and is sufficient to produce angiogenesis 34,35 . Interestingly, TLRs activation not only initiates innate and adaptive immune responses but also regulates angiogenesis after binding to exogenous and endogenous ligands 8,14,36 . Our study showed that hypoxia induced the expression of VEGFA, and overexpression of VEGFA in WT mice promoted angiogenesis as demonstrated by an increase in capillary and arteriole densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation